The cranial morphology of the limbless skink Melanoseps ater rondoensis - Boyd, E. W. S.(Eric William Stuart) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1969.